2022
DOI: 10.1093/cid/ciac104
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Stewardship Strategies and Their Association With Antibiotic Overuse After Hospital Discharge: An Analysis of the Reducing Overuse of Antibiotics at Discharge (Road) Home Framework

Abstract: Background Strategies to optimize antibiotic prescribing at discharge are not well understood. Methods In fall 2019, we surveyed 39 Michigan hospitals on their antibiotic stewardship strategies. The association of reported strategies with discharge antibiotic overuse (unnecessary, excess, suboptimal fluoroquinolones) for community-acquired pneumonia (CAP) and urinary tract infection (UTI) was evaluated in two ways: 1) all str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…A 2022 study evaluating antibiotic stewardship strategies for optimizing therapy at hospital discharge found discharge-specific strategies may have the greatest impact on lowering antibiotic overuse at discharge. 18 In a single-center study implementing a pharmacist-driven antibiotic timeout at discharge, the intervention was feasible and decreased inappropriate antibiotic use. 17 Another pharmacist-driven transition of care model implemented in multiple facility types was also associated with improved antibiotic prescribing at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…A 2022 study evaluating antibiotic stewardship strategies for optimizing therapy at hospital discharge found discharge-specific strategies may have the greatest impact on lowering antibiotic overuse at discharge. 18 In a single-center study implementing a pharmacist-driven antibiotic timeout at discharge, the intervention was feasible and decreased inappropriate antibiotic use. 17 Another pharmacist-driven transition of care model implemented in multiple facility types was also associated with improved antibiotic prescribing at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Covariate-constrained randomization allows for balancing of multiple pre-specified characteristics of interest when the number of characteristics is high compared to the number of clusters being randomized [ 40 ]. Characteristics that will be included in the constrained randomization process include (a) baseline antibiotic overuse at discharge; (b) year of entry into HMS; (c) social needs of population being served by the hospital (classified as rural hospital) (defined as either somewhat or very rural using Rural Urban Continuum Code (RUCC) score > 3) [ 41 ], Minority Serving Hospital or Safety Net Hospital (defined as hospital with RUCC score of 1 or 2 and either top 25% non-white and/or Hispanic population or top 25% Medicaid or uninsured population, respectively) [ 42 ] or neither; (d) composition of ASP leadership (is the ASP team led by both an ID physician and an ID pharmacist or not); and (e) baseline number of stewardship interventions already implemented (weighted using our published ROAD Home framework) [ 35 ]. We will select from randomization sequences that have a balance of ± 10% or ± 2 sites between arms for continuous and categorical variables, respectively.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Evidence-based antibiotic stewardship interventions often involve individual or combinations of discrete strategies (e.g., prospective audit and feedback, updated guidelines, clinician education, behavioral nudges, clinical decision support) to move evidence-based prescribing practices (guideline-concordant antibiotic use—the right drug for the right diagnosis, at the right dose, for the right duration) [ 33 ] into routine clinical practice by changing clinician behavior [ 34 ]. 1 In the case of discharge antibiotic stewardship interventions, emerging evidence suggests there are different pathways to improve antibiotic use that vary widely in feasibility [ 35 ]. Supporting hospitals in selecting evidence-based stewardship interventions tailored to their local context is likely more feasible and effective for diverse hospitals than a “one size fits all” approach to antibiotic stewardship at discharge which suggests, for example, that all hospitals should implement an ID pharmacist-led audit and feedback program [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…With community acquired pneumonia (CAP), Dinh et al showed that discontinuation of beta lactam therapy at 3 days in noncritical care wards was noninferior to 8 days (77% vs 68%) with less adverse events and a shorter length of stay [17 ▪▪ ]. Unfortunately, antibiotics could be unnecessarily extended on discharge thereby giving a longer course than needed [18 ▪ ]. Vaughn et al showed that despite inpatient antimicrobial stewardship (ASP) work, extension of antibiotic use for CAP and urinary tract infections (UTI) were common on discharge.…”
Section: Shorter Durations Of Antibiotic Therapymentioning
confidence: 99%
“…Vaughn et al showed that despite inpatient antimicrobial stewardship (ASP) work, extension of antibiotic use for CAP and urinary tract infections (UTI) were common on discharge. Having a broader ASP approach that addresses discharge antibiotics to include durations already received as an inpatient [18 ▪ ]. Other diseases where shorter courses have been well accepted or should be implemented are ventilator associated pneumonia [19 ▪ ], osteomyelitis [20 ▪ ,21 ▪ ] and UTI [22 ▪ ].…”
Section: Shorter Durations Of Antibiotic Therapymentioning
confidence: 99%